At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

find the value of m. (-3/4)-⁴×(-3/4)-¹¹ = (-3/4)^m​

Sagot :

Answer:

m = - 15

Step-by-step explanation:

Using the rule of exponents

[tex]a^{m}[/tex] × [tex]a^{n}[/tex] = [tex]a^{(m+n)}[/tex] , then

[tex](-\frac{3}{4}) ^{-4}[/tex] × [tex](-\frac{3}{4}) ^{-11}[/tex] = [tex](-\frac{3}{4}) ^{m}[/tex] , that is

[tex](-\frac{3}{4}) ^{(-4-11)}[/tex] = [tex](-\frac{3}{4}) ^{m}[/tex]

[tex](-\frac{3}{4}) ^{-15}[/tex] = [tex](-\frac{3}{4}) ^{m}[/tex]

Equating exponents gives

m = - 15